2021
DOI: 10.3390/ma14112721
|View full text |Cite
|
Sign up to set email alerts
|

Study on Kinetics of Transformation in Medium Carbon Steel Bainite at Different Isothermal Temperatures

Abstract: Ultra-fine carbide-free bainitic (UCFB) steel, also known as nano-bainite (NB) steel, is composed of bainitic ferrite laths with nanoscale thickness and carbon-rich film-like retained austenite located between laths. The bainite transformation kinetic model can accurately describe the bainite transformation kinetics in conventional austempering (CA) processes based on the shear mechanism combined with the dilatometer test. UCFB steels with medium and high carbon composition are designed in this work to systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The microstructural morphology of the three specimens is shown and compared in Figure 4. The bainite transformation kinetics of the specimen austempered at 300 • C are reported in the literature [37]. When the volume fraction of prior ferrite in the intercritical zone increases from 0 to 9.6%, the incubation time (completion time) of the bainite transformation decreases from 1364 s (5.3 h) to 687 s (1.7 h).…”
Section: Dilatometric Analysismentioning
confidence: 99%
“…The microstructural morphology of the three specimens is shown and compared in Figure 4. The bainite transformation kinetics of the specimen austempered at 300 • C are reported in the literature [37]. When the volume fraction of prior ferrite in the intercritical zone increases from 0 to 9.6%, the incubation time (completion time) of the bainite transformation decreases from 1364 s (5.3 h) to 687 s (1.7 h).…”
Section: Dilatometric Analysismentioning
confidence: 99%
“…[7] Hence, lowering transformation temperature is used to refine CFB microstructure and reduce the amount of blocky RA, but it makes the transformation time too long due to extremely slow bainitic formation kinetics at low temperature. [11] In this context, aircooled bainitic steels have been developed to save energy and reduce CO 2 emission during manufacturing process. [12][13][14][15] It is reported that the air-cooled bainitic steels exhibit high strength and toughness when the alloying is appropriately designed.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies and diverse processing approaches have been carried out to alter the microstructure of alloy steel and improve its impact resistance, stiffness, wear resistance, and strength [7][8][9][10][11][12]. Abbasi et al analyzed the microstructural features of three different types of medium carbon steel (namely, MnCrB-, NiCrSi-, and NiCrMoV-bearing steels) and found that the addition of small amounts of alloying elements and varying austenitic grain sizes were mainly responsible for the changes in the microstructure and mechanical properties of the steel [13].…”
Section: Introductionmentioning
confidence: 99%